The Cognitive Neuroscience of Problem – Solving and Creativity: Implications for the Nigerian Secondary School Teacher - Iyagba, P. W; Briggs, Victor D (Research Parks Publishers, 2021)
Cognitive neuroscience is a subfield of neuroscience that studies the physiological basis of cognition. Cognition is the process of knowing, thatinvolves the reception of raw sensory information and the transformation, elaboration, storage, recovery and use of the information. Cognitiondepends on the workings of the nervous system and is directly concerned about intellectual function. Problem–solving and creativity are twocognitive processes that help the individual harmonize information for solving problems and generate novel ideas and innovative solutions toproblems. Problem–solving is thinking that is directed towards the solving of a specific problem which may involve both the formation ofresponses and the relation among positive responses. Creativity is the ability to produce novel ideas and innovative solutions to problems. Thecerebral cortex and the prefrontal cortex of the human brain are mainly involved in the cognitive processes of problem–solving and creativity.The cognitive theory of problem–solving are creativity and the four– model of creativity form the theoretical thrust of this study.